Berlin diaries, 1940-1945 - Vassiltchikov, Marie 1917-1978 (Vintage Books, 1988)
The secret diaries of a twenty-three-year-old White Russian princess who worked in the German Foreign Office from 1940 to 1944 and then as a nurse, these pages give us a unique picture of wartime life in that sector of German society from which the 20th of July Plot, the conspiracy to kill Hitler, was born